Improvement Of Increasing Labor Efficiency In Industrial Enterprises Based On The Experience Of Developed Countries (Global Scientific Review, 2025)
The article widely covers the issues of ensuring the development of extensive experience and knowledge, taking into account relevant interests and goals for the use and development of personnel labor based on foreign experience. The labor payment system and its advantages are also analyzed